Advancing human health risk assessment. (8th July 2019) - Lanzoni, Anna; Castoldi, Anna F; Kass, George EN; Terron, Andrea; De Seze, Guilhem; Bal‐Price, Anna; Bois, Frédéric Y; Delclos, K Barry; Doerge, Daniel R; Fritsche, Ellen; Halldorsson, Thorhallur; Kolossa‐Gehring, Marike; et al.
Abstract: The current/traditional human health risk assessment paradigm is challenged by recent scientific and technical advances, and ethical demands. The current approach is considered too resource intensive, is not always reliable, can raise issues of reproducibility, is mostly animal based and does not necessarily provide an understanding of the underlying mechanisms of toxicity. From an ethical and scientific viewpoint, a paradigm shift is required to deliver testing strategies that enable reliable, animal‐free hazard and risk assessments, which are based on a mechanistic understanding of chemical toxicity and make use of exposure science and epidemiological data. This shift will require a new philosophy, new data, multidisciplinary expertise and more flexible regulations. Re‐engineering of available data is also deemed necessary as data should be accessible, readable, interpretable and usable. Dedicated training to build the capacity in terms of expertise is necessary, together with practical resources allocated to education. The dialogue between risk assessors, risk managers, academia and stakeholders should be promoted further to understand scientific and societal needs. Genuine interest in taking risk assessment forward should drive the change and should be supported by flexible funding. This publication builds upon presentations made and discussions held during the break‐out session 'Advancing risk assessment science – Human health' at EFSA's third Scientific Conference 'Science, Food and Society' (Parma, Italy, 18–21 September 2018).